Новый вид моли рода Roeslerstammiia (Lepidoptera, Roeslerstamiidae) из юго-восточного Забайкалья - Будашкин, Ю.И.; Костюк, И.Ю. (Вестник зоологии, 1993)
Roeslerstammia durulgucnsis Budashkin et I. Kostju k, sp. n. is described from Dahuria, type locality: Dahuria, Ermana mis. Type is deposited in Kiev University Zoological Museum.